Prevention of carcinogenesis and metastasis by artemisinin-type drugs - Abba, Mohammed L.; Patil, Nitin; Leupold, Jörg; Allgayer, Heike (Cancer letters, 2018)
Artemisia annua (sweet wormwood, qinhao) is an ancient Chinese herbal remedy for pyrexia. Nowadays, artemisinin (qinghaosu) and its derivatives belong to the standard therapies against malaria worldwide, and its discovery has led to the Nobel Prize in Physiology and Medicine to Youyou Tu in 2015. While most attention has been paid to the treatment of malaria, there is increasing evidence that Artemisinin-type drugs bear a considerable potential to treat and prevent cancer. Rather than reporting on therapy of cancer, this review gives a comprehensive and timely overview on the chemopreventive effects of artemisinin and its derivatives against carcinogenesis and metastasis formation, following the multistage model of carcinogenesis (initiation, promotion, progression). The favorable toxicity profile known from malaria studies indicates that artemisinin-type drugs may be safely applied to prevent carcinogenesis and cancer metastasis in human beings.
Gesehen am 02.04.2019